The Effect Of Sea Cucumber Powder And Hyperbaric Oxygen Therapy On The Expression Of Tumor Necrosis Factor Alfa In Rats With Diabetes Mellitus Induced By Porphyromonas gingivalis - Caroline Prajnaparamitha Anggraini; Kristanti Parisihni; Widyastuti (Denta Journal Kedokteran Gigi, 2016)
Background: Periodontitis have a bidirectional relationship with diabetes mellitus, both can increase oxidative stress that trigger an increase of pro-inflammatory cytokines, such as TNF-α. Sea cucumbers have anti-inflammatory component that act to inhibit the release of inflammatory mediators. Hyperbaric oxygen therapy reduce oxidative stress. Purpose: The aim of this study is to investigate the effect of the sea cucumber powder and hyperbaric oxygen therapy on the expression of TNF-α in rats with diabetes mellitus induced by P.gingivalis bacteria. Materials and Methods: The study was an experimental laboratories research with factorial design. Twenty wistar rats were divided into 5 groups. K0 negative control, K1 positive control. K1-K4 groups were induced with streptozotocin for diabetes condition and P.gingivalis bacteria for periodontitis condition. K2 group was treated with seacucumber 3% for 7 days, K3 with OHB 2.4 ATA 3 x 30’ interval 5’ for 7 days, and K4 group was treated with combination of sea cucumber and OHB. At the 51 st day all rats were sacrified, then the expression of TNF-α on periodontal macrophages were examined by immunohistochemistry stain. Data were analized by Kruskal Wallis followed by Mannwhitney. Result: Expression of TNF-α were increased in K1 (11.50±1.291) compare K0 (p<0.05). Sea cucumber treatment, OHB, and combination treatment decreased expression of TNF-α significantly in amount of 2.50±0.577 (K2), 8.25±2.217 (K3), 3.00±0.816 (K4). Conclusion: Sea cucumber powder and OHB therapy affected the expression of TNF-α in rats with diabetes mellitus induced by P. gingivalis bacteria.